Manajemen Domestik Rumah Tangga Wanita Muslimah Dalam Ajaran Sunnah - Jannah Lukman (Jurnal Studi Hadis Nusantara, 2020)
Muslim women couldn’t be separated essentially with domestic household affairs. Definitely, this matter has not gone unnoticed by the Hadith that touches all of the part of muslim life. Muslim women also have a role as the leaders in domestic affairs and will be held accountable in the hereafter. This study is here to explain how the Sunnah has guided muslim women long time ago to be successful in domestic household affairs. This study also aimed to detail the Hadiths related to the domestic principles of muslim women households. This study used the thematic Hadith study method to focus and discover the basic concepts of domestic muslim women household management that already exist in the teachings of the Sunnah. After doing research, it was found that there are as many twenty Hadiths related to this matter. This study also found the basis for domestic management of muslim women households consists of: love to take care of the household; serving husbands and caring for children; keep the bathroom; tidying up the kitchen; prevent animal nests in the house; dress up for husband, obey him and support him; tidying up the lights before going to bed at night; decorate the room of the house; keep the husband from being attracted to other women; ask permission when leaving the house; willing to breed a lot. It is hoped that this study will add to the wealth of knowledge for muslim women to remain cheerful and successful in managing domestic and household affairs.